Penerapan Model Pembelajaran Team Based Project Untuk Meningkatkan Hasil Belajar Tematik Siswa Kelas IV SDN 104252 Sei Tuan T.A 2022/2023 - Mahyaruddin Zaky, Irfan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Based on observations in class IV SDN 104252 Sei Tuan learning outcomes in thematic learning, especially theme 1 in understanding the Main and Supporting material, Sound Energy, and specifically in Social Religion material. This study aims to improve student learning outcomes by applying the Team-Based Project learning model to the subject matter of Basic and Supporting Infrastructure, Sound Energy. This type of research is "Classroom Action Research". The subjects of this study were fourth-grade students of SD Negeri 104252 Sei Tuan who collected 23 students consisting of 12 male students and 11 female students, while the objects in this study were student learning outcomes in thematic learning by applying the Team-Based Project learning model. . This research was conducted in 2 cycles, namely cycle I and cycle II, each cycle consisting of 1 meeting, with 4 stages namely planning observation, and reflection. Data collection techniques used are tests, observation sheets, and documentation. What is being analyzed is the test data and observation data during the learning process takes place. Based on this research shows learning outcomes that have increased in each cycle. In the initial observation data (pre-test) from 23 students, 7 students had completed their studies with a proportion of 30.43% completeness and for students who did not complete, there were 16 students with a proportion of 69.57% and classified as a very poor category. Then followed in cycle I there was 14 students with a completeness percentage of 60.87% and students who did not complete there were 9 students with a proportion of 39.13% belonging to the category of not fulfilling classical completeness. Then in cycle II, 20 students completed with a completeness percentage of 86.96%, and students who did not complete 3 students with a percentage of 13.04% were classified as very good categories. From the research data above, it can be obtained that student learning outcomes increase with the application of the Team-Based Project learning model to thematic learning theme 1 The Beauty of Togetherness in the Main Material and Supporting Infrastructure, Sound Energy. It is recommended that teachers also apply the Team-Based Project learning model in the learning process, especially in thematic learning in class IV.